1996
DOI: 10.1111/j.1469-7998.1996.tb05424.x
|View full text |Cite
|
Sign up to set email alerts
|

Millipede communities in rehabilitating coastal dune forests in northern KwaZulu/Natal, South Africa

Abstract: With 1 figure in the text)The rehabilitation, after mining, of coastal sand dunes north of Richards Bay by Richards Bay Minerals began some 18 years ago, and resulted in the simultaneous availability of a known-aged series of stands representative of coastal dune forest succession.A survey of the millipede community in this area revealed increases in species diversity and a decrease in their density, with an increase in stand age. Development of these communities is characterized by replacement and addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Previous studies of soil and litter fauna development in re‐vegetated sites have reported an initial colonisation by species tolerant of harsh environmental conditions (e.g. Fox & Fox, 1982; Andersen, 1993; van Aarde et al. , 1996; Dunger et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of soil and litter fauna development in re‐vegetated sites have reported an initial colonisation by species tolerant of harsh environmental conditions (e.g. Fox & Fox, 1982; Andersen, 1993; van Aarde et al. , 1996; Dunger et al.…”
Section: Discussionmentioning
confidence: 99%
“…For millipedes the differences in the width of edges between sampled sites may be due to increasing variation in the physiognomic structure with an increase in regeneration age, implying increases in structural heterogeneity and soil organic content (see van Aarde et al 1998). This is not surprising, however, because the rehabilitating area is considered to be following a pathway of secondary succession (van Aarde et al 1996a). During secondary succession the structural heterogeneity of a site will increase due to the formation of subcanopy layers and increasing gap formation (Bierregaard et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Sampling of millipedes consisted of searching through litter and shrub strata and observing the tree strata for millipedes. Sampling was conducted from 28 October to 28 November 1997 from dawn to 1100 hr, this representing the peak period of millipede activity (van Aarde et al 1996a). Sampling of transects continued until the coefficient of variation of density estimates reached a plateau.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies across the successional sere of rehabilitating coastal vegetation suggested age-related convergence towards old-growth dune forest in both compositional and structural properties of tree, herb, millipede and bird assemblages (van Aarde et al 1996b;1996c;Kritzinger and van Aarde 1998;Redi et al 2005;Wassenaar et al 2005). By contrast, trends in small mammal and dung beetle assemblages were contradictory in suggesting either convergence or non-convergence (Ferreira and van Aarde 1997;Davis et al 2003;Wassenaar et al 2005).…”
Section: Introductionmentioning
confidence: 98%